Methodology of Using Hadeeth in Kawniyyah Verses Interpretation by Muhammad Al-Amin Al-Harari: An Observation - Mohammed Akhiruddin Ibrahim (Center for Promoting Ideas (CPI), USA, 2024)
The study focuses on the review of the methodology used in the interpretation of hadeeth of Kawniyyah verses in the Holy Quran by Sheikh Muhammad al-Amin al-Harary in his Tafseer Hada'iq al-Rawh wa al-Rayhan fi Rawabi 'Ulum al-Qur'an. It involves an observation on the hadeeth used by the author in interpreting texts related to the heavens and the earth, natural phenomena including clouds, rain, wind, thunder, lightning and gravity, day and night creations, the creation of mankind, astronomy, animals, plants vegetation, oceans, minerals, geography and medicine. Hadeeth used by him in the interpretation of the verses will be grouped according to the Kawniyyah aspects mentioned. In order to get a clearer meaning, it is translated into English. Then a brief reference is made (takhrij) in order to know who recorded the hadeeth and its quality. Finally, a general survey is made in relations to the author’s methodology of using hadeeth in his interpretation of the verses.